PENERAPAN STRATEGI BALANCED SCORECARD DALAM UPAYA MENINGKATKAN KINERJA MANAJEMEN - Sulistiyanto, Dandy Dwi; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The research is aimed to find out how the performance of the management is measured by using BalancedScorecard method from each perspective in order to be align with the vision, mission and company strategies.This research has been conducted at PT. Karya Manunggal Jati. The research method is descriptive qualitative.The result of the research shows that the implementation of Strategy Map which is illustrated in Figure 3 andperformance measurement by using the balanced scorecard has good constribution to the company with thefinancial perspective which has been proven by the realization of 2012, 2013 and 2014 financial perspective,Return on Investment (ROI) of 11.12%, 10.90% and 17.56%, Profit Margin on Sales of 1.36%, 1.47% and2.54% and Sales Growth Rate of 12.35% and 5.40%, Meanwhile, the customer perspective shows 66.7% isstated to be good, that the evidences of the survey which have been realized in 2012, 2013 and 2014, CustomerRetention of 5.9%, 6.25% and 6.67%; Number of New Customers of 19,44%, 6,98% dan 10,87%. Number ofcomplaint of 2.1%, 0.15% and 0.06%, For perspective, the internal business process has been proven by the2012, 2013 and 2014 realization, On Time Delivery of 99.91%, 99.94% and 99.50%. It can be concluded thatwith the implementation of the Balance Scorecard so it is synchronized with the vision and mission of theorganization.Keywords: Performance measurement, balanced scorecard, strategy map.